Urgensi Teknologi Pendidikan : Analisis Kelebihan Dan Kekurangan Teknologi Pendidikan Di Era Revolusi Industri 4.0 - Imroatul Ajizah; Munawir Munawir (stit-islamic-village, 2021)
Technology has penetrated various sides of human life, including in the field of education. Technology in education offers a variety of systematic ways to conceptualize planning, implementation, and evaluation in the educational process. In other words, educational technology helps learning using modern learning techniques. This study uses a research library research method by looking for references related to the title. The findings of this study are that the application of appropriate and ethically appropriate technology can improve performance and learning outcomes that have an impact on improving the quality of education. The author assesses that it is very important to apply technology in the field of education as a facilitator to facilitate all educational processes, so that educational needs can be met effectively and efficiently. Sophisticated technology does not necessarily have a positive impact, but also has a negative impact. So it is necessary to consider in selecting technology and finding solutions related to the use of educational technology so that it can function optimally.